2010
DOI: 10.1359/jbmr.090724
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in monocytes and SNP association suggest the importance of the STAT1 gene for osteoporosis in both Chinese and Caucasians

Abstract: Osteoporosis is characterized mainly by low bone mineral density (BMD). Many cytokines and chemokines have been related with bone metabolism. Monocytes in the immune system are important sources of cytokines and chemokines for bone metabolism. However, no study has investigated in vivo expression of a large number of various factors simultaneously in human monocytes underlying osteoporosis. This study explored the in vivo expression pattern of general cytokines, chemokines, and their receptor genes in human mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
(88 reference statements)
0
44
0
Order By: Relevance
“…There is strong evidence that STAT1 is significant in bone metabolism as STAT1 has been reported to be upregulated in the femur tissue of osteoporotic mice (27) and humans (18). STAT1 may serve as a primary mediator of interferon (IFN) signaling pathways involving osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence that STAT1 is significant in bone metabolism as STAT1 has been reported to be upregulated in the femur tissue of osteoporotic mice (27) and humans (18). STAT1 may serve as a primary mediator of interferon (IFN) signaling pathways involving osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts produce and secrete osteoprotegerin, a decoy receptor that binds to RANKL and blocks RANKL/RANK interactions and hence suppresses the ability of RANK to increase bone resorption (9). Previous studies have shown that blood monocytes also produce a wide variety of inflammatory factors and transcription factors involved in bone metabolism, including interleukin-1 (10), tumor necrosis factor-α (TNF-α) (11), interleukin-6 (12), platelet-derived growth factor (13), transforming growth factor-β (14), resolvinE1 (15), runt-related transcription factor 2 (Runx2; 16), guanylate binding protein 1 (GBP1), signal transducer and activator of transcription 1 (STAT1), CXC chemokine ligand 10 (CXCL10) (17), chemokine receptor 3, histidine decarboxylase and glucocorticoid receptor genes (18).…”
Section: Introductionmentioning
confidence: 99%
“…The RANKL-independent pathway is likely mediated by proinflammatory cytokines, such as IL-1 and TNF-α, which are enriched in the bone microenvironment of acute Charcot's osteoarthropathy [104]. In addition to these in vitro osteoclastic characterization studies, freshly isolated PBMs have also been used to investigate the in vivo molecular mechanisms underlying the abnormal osteoclastic activity associated with various skeletal disorders [2,[105][106][107][108][109]. By comparing the transcriptomewide gene expression profiles of PBMs freshly isolated from subjects with high versus low bone mineral density (BMD) values, we [2] identified 66 differentially expressed genes.…”
Section: Using Pbms As a Working Cell Model To Study For Bone Diseasesmentioning
confidence: 99%
“…They are precursors of osteoclasts 4) and also secrete osteoclastogenic factors such as IL-1, IL-6, and TNF-a. 5) Human studies have also shown relationships between the expression levels of certain genes in circulating monocytes and osteoporosis: annexin A2, 6) signal transducer and activator of transcription 1, 7) chemokine (C-C motif) receptor 3, histidine decarboxylase, and glucocorticoid receptor. 8) Long non-coding RNA (LncRNA) is an RNA molecule that is longer than 200 nucleotides and is not translated into a protein, 9) although these long non-coding transcripts were once considered to be simply transcriptional "noise" or cloning artifacts.…”
mentioning
confidence: 99%